Effectiveness of humanitarian logistics training: The Finnish Red Cross (FRC) Emergency Response Unit (ERU). Issue 2 (1st November 2019) - Heaslip, Graham; Stuns, Karl-Kristian
Abstract : Purpose: The purpose of this paper is to evaluate the effectiveness of humanitarian logistics training for the Finnish Red Cross (FRC) Emergency Response Unit (ERU) delegates, and the factors that influence its success. The managerial purpose of this research is to support the FRC in improving their Logistics ERU Foundation training. Additionally, this research provides humanitarian organisations, engaged in emergency response efforts, insights for logistics training design. Design/methodology/approach: This is a case study examining the FRC, with qualitative data being collected in a field study, utilising participant observation and in-context interview techniques for rich data collection. Findings: This research evaluated the effectiveness of the Logistics ERU Foundation training of the FRC by adapting the four-level training evaluation model by Kirkpatrick and transfer of training theories. The research has contributed to Gralla et al. 's (2015) call for further research in evaluating what people learn from humanitarian logistics trainings and in documenting and sharing experiences with specific training programs. Practical implications: The conceptual framework serves as a basis for exploratory qualitative investigation of training transfer, from the perspectives of trainees, facilitators and human resource personnel. Originality/value: This research contributes to the humanitarian community by identifying gaps in Red Cross Logistics ERU training and to the development of curricula content relating to Red Cross logistics response phase operations. Additionally, this gives other humanitarian organisations, operating in the response phase of natural disasters, insights for logistics training design.